2022
DOI: 10.1111/1440-1703.12319
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and seasonal variation of plant taxa detected in faces of Cervus nippon yakushimae based on plant DNA analysis in Yakushima Island

Abstract: Recently, plant DNA analysis of feces has been successfully used to evaluate the food species composition of sika deer Cervus nippon. Here, we applied this method to Yaku‐sika C. nippon yakushimae, which increased its population and had a great negative impact on understory vegetation in Yakushima Island. We identified food plants of C. nippon yakushimae by sequencing chloroplast DNA fragments (rbcL region) of plants remaining in feces collected in the field in April, June, August, and October 2018, using a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…For instance, a previous study in woodrats showed an increase in microbiome diversity associated with intake of PSCs, which is considered to be the result of adaptation to plant toxins 50 . Recent studies showed that Yaku sika selectively forages small plants in understory vegetation, if they are available, and also utilize evergreen tall trees 28 , 29 . Among the evergreen trees, Fagaceae and Lauraceae (in specific, Machilus spp.)…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, a previous study in woodrats showed an increase in microbiome diversity associated with intake of PSCs, which is considered to be the result of adaptation to plant toxins 50 . Recent studies showed that Yaku sika selectively forages small plants in understory vegetation, if they are available, and also utilize evergreen tall trees 28 , 29 . Among the evergreen trees, Fagaceae and Lauraceae (in specific, Machilus spp.)…”
Section: Resultsmentioning
confidence: 99%
“…In low deer density areas, the availability of the small plants is higher and more species-rich understory vegetation is found, thus the dependence of Yaku sika on food derived from tall trees is lower in those areas 27 . The deer in high density areas have expanded their feed to include tannin-rich unpalatable plants, fallen leaves 27 , 54 , and woody material to meet their nutritional needs 28 , 34 . Thus, the higher diversity of RBM in Yaku sika under high population density may enable deer to scavenge a wider variety of plants and tolerate plant toxins, thus maintain nutritional status even under high density conditions 29 , 55 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations